2019
DOI: 10.3847/1538-4357/ab50b5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Constraints from the Redshift Dependence of the Alcock–Paczynski Effect: Fourier Space Analysis

Abstract: The tomographic Alcock-Paczynski (AP) method utilizes the redshift evolution of the AP distortion to place constraints on cosmological parameters. It has proved to be a robust method that can separate the AP signature from the redshift space distortion (RSD) effect, and deliver powerful cosmological constraints using the 40h −1 Mpc clustering region. In previous works, the tomographic AP method was performed via the anisotropic 2-point correlation function statistic. In this work we consider the feasibility of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…). Luo et al (2019) studied the feasibility of using the redshift evolution of the galaxy power spectrum m D P k ˆ( ) to conduct the tomographic AP test. They found that the impacts of halo bias and RSD play only a minor role in the shape distortion in the Fourier space compared to the AP effect.…”
Section: A Review Of the Ap Test-related Studiesmentioning
confidence: 99%
“…). Luo et al (2019) studied the feasibility of using the redshift evolution of the galaxy power spectrum m D P k ˆ( ) to conduct the tomographic AP test. They found that the impacts of halo bias and RSD play only a minor role in the shape distortion in the Fourier space compared to the AP effect.…”
Section: A Review Of the Ap Test-related Studiesmentioning
confidence: 99%
“…Measurements of the galaxy PS or CF have provided exquisite constraints on the expansion history of the Universe via the Baryon Acoustic Oscillations (BAO) [7][8][9] and the Alcock-Paczynski effect [10][11][12][13][14][15][16], and on the growth of structure via Redshift Space Distortions (RSD) [17][18][19][20][21]. In many of these works, the observed statistic are compared with analytic models, templates or more numerical perturbation theory predictions.…”
Section: Introductionmentioning
confidence: 99%